Insufficient natural killer cell responses against retroviruses: how to improve NK cell killing of retrovirus-infected cells. Issue 1 (December 2016) - Littwitz-Salomon, Elisabeth; Dittmer, Ulf; Sutter, Kathrin
Abstract Natural killer (NK) cells belong to the innate immune system and protect against cancers and a variety of viruses including retroviruses by killing transformed or infected cells. They express activating and inhibitory receptors on their cell surface and often become activated after recognizing virus-infected cells. They have diverse antiviral effector functions like the release of cytotoxic granules, cytokine production and antibody dependent cellular cytotoxicity. The importance of NK cell activity in retroviral infections became evident due to the discovery of several viral strategies to escape recognition and elimination by NK cells. Mutational sequence polymorphisms as well as modulation of surface receptors and their ligands are mechanisms of the human immunodeficiency virus-1 to evade NK cell-mediated immune pressure. In Friend retrovirus infected mice the virus can manipulate molecular or cellular immune factors that in turn suppress the NK cell response. In this model NK cells lack cytokines for optimal activation and can be functionally suppressed by regulatory T cells. However, these inhibitory pathways can be overcome therapeutically to achieve full activation of NK cell responses and ultimately control dissemination of retroviral infection. One effective approach is to modulate the crosstalk between NK cells and dendritic cells, which produce NK cell-stimulating cytokines like type I interferons (IFN), IL-12, IL-15, and IL-18 upon retrovirus sensing or infection. Therapeutic administration of IFNα directly increases NK cell killing of retrovirus-infected cells. In addition, IL-2/anti-IL-2 complexes that direct IL-2 to NK cells have been shown to significantly improve control of retroviral infection by NK cells in vivo. In this review, we describe novel approaches to improve NK cell effector functions in retroviral infections. Immunotherapies that target NK cells of patients suffering from viral infections might be a promising treatment option for the future.